Challenges of Policy Implementation in Monitoring and Evaluation of Teaching and Learning in Nigerian Primary Schools - Fatima Moromoke Adeyemo; Afeez Adeshina Shittu; Olubunmi Oludiran Moradeke; Lydia Ahonkhai Grace (Universitas Islam Bunga Bangsa Cirebon, 2025)
The quest for quality assurance in Nigerian primary education has intensified due to the critical role education plays in national development and global competitiveness. Effective teaching and learning depend largely on continuous assessment, monitoring, and evaluation to ensure that pupils acquire the intended knowledge and skills. However, despite policy provisions, the implementation of these practices in Nigerian primary schools faces numerous challenges that undermine educational outcomes. The research examines the relevance of assessment, monitoring, and evaluation in teaching and learning at the primary school level and identifies the key challenges hindering their effective policy implementation. A conventional literature review approach was adopted, drawing on 25 peer-reviewed articles purposively selected from databases including Google Scholar, ResearchGate, Academia, and PubMed. The studies were screened for relevance, methodological rigour, and alignment with the research focus. Data were synthesised thematically using social constructivism and project execution theory as guiding frameworks. Findings revealed that continuous assessment, monitoring, and evaluation are essential for enhancing teacher effectiveness, learner achievement, accountability, and transparency in primary education. Nonetheless, their implementation is impeded by challenges such as inadequate teacher training, poor funding, weak record management, negative teacher attitudes, a shortage of qualified evaluators, and a lack of a standardised monitoring framework. It was concluded that addressing these barriers through periodic teacher training, improved funding, professionalisation of monitoring roles, and establishment of logical frameworks can strengthen compliance with policy goals. This contributes to ensuring sustainable quality assurance practices and improved learning outcomes in Nigerian primary schools.